IMPLEMENTATION OF VIOLENCE PREVENTION AND HANDLING POLICIES IN DIPONEGORO UNIVERSITY (CASE STUDY FROM FACULTY OF PSYCHOLOGY, FACULTY OF ENGINEERING, AND FACULTY OF SOCIAL AND POLITICAL SCIENCES) - Narwastu Alma; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
Violence in higher education environments, including physical and psychological violence, bullying, sexual violence, discrimination, intolerance, as well as repressive policies, is a crucial issue that impacts the safety and well-being of the academic community. Ministry of Education, Culture, Research, and Technology Regulation Number 55 of 2024 mandates that every university establish a Task Force for the Prevention and Handling of Violence (PPKPT) as an effort to strengthen preventive and responsive measures against various forms of violence on campus. This study aims to analyze the implementation of policies for the prevention and handling of violence at Diponegoro University through a case study on the Faculty of Psychology, Faculty of Engineering, and Faculty of Social and Political Sciences. A descriptive qualitative approach is employed, with data collection techniques including interviews, documentation, and observation. Data analysis was conducted using George C. Edwards III’s policy implementation model, which includes the variables of communication, resources, disposition, and bureaucratic structure. The research findings indicate that policy implementation has taken place, but has not yet reached an optimal level due to limitations in human resources, insufficient dissemination of information concerning regulations, and a lack of integrated reporting mechanisms. Nevertheless, institutional commitment and regulatory support emerged as key factors driving policy implementation. These findings are expected to provide strategic recommendations for strengthening governance in the prevention and management of violence in higher education environments.